Etika dan Kode Etik Jurnalistik dalam Media Online Islam - Iim Rohimah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2017)
Online media is a new world’s phenomenon which produce the mass communication subjects which is not only institutionalized but also individuals, famously known as citizen journalist. However, this new type of journalist is considered as not professional as mainstream journalists. This phenomenon is also happened in islamic online media, which the subject of this communication could be an institution, or either individuals. These subjects are often violating journalism rule and ethics on the internet. The ideology of this writer and institution could be expressed on a discriminative and unfair journalism product. On the other hand, religious sentiment could also be a factor when a journalism products tend to accused a person before the law. This condition has to be evaluated, it is due to the islamic media on the internet could be an image of Islamic world as a whole. Moreover as a moslem, we are not only pay attention to the journalism code but also on Islamic value. There are many Islamic rule which stated that journalism activities linked with taqwa concept. Each of journalism activites on the media has to be based on the fairness, carefulness and critique-constructive concept. With that, it could strengthen moslem activities on holding not only towards journalism code of ethics but also Islamic religious faith.